Porosity and bioactivity of hydroxyapatite-glass composites - Skorokhod, V.V.; Ivanchenko, L.A.; Pinchuk, N.D.; Getman, O.I.; Solonyn, S.M.; Panichkina, V.V.; Radchenko, P.Ja. (Functional Materials, 2006)
Composition, manufacturing method, and some properties of composite ceramics for medical purposes on the basis of bone apatite has been described. The studies include determination of pycnometric density, porosity, and bioactivity degree of composites with various mass ratios of crystalline and amorphous phases depending on sintering conditions. Some results of tests in vivo are presented, the influence of the glassy phase presence in the implants on the bone regeneration rate and size of the implanted biomaterial granules is noted. Описано склад, спосiб одержання i ряд властивостей композитної керамiки медичного призначення на основi кiсткового апатиту. Дослiдження мiстять визначення пiкнометричної густини, пористостi i ступеню бiоактивностi композитiв з рiзним масовим спiввiдношенням кристалiчної i аморфної фаз в залежностi вiд умов спiкання. Представлено деякi результати випробувань in vivo, вiдзначено вплив присутностi скло-фази в iмплантатах на швидкiсть регенерацiї кiстки та розмiри iмплантованих гранул бiоматерiалу. Описан состав, способ получения и ряд свойств композитной керамики медицинского назначения на основе костного апатита. Исследования включают определение пикно-метрической плотности, пористости и степени биоактивности композитов с разным массовым соотношением кристаллической и аморфной фаз в зависимости от условий спекания. Представлены некоторые результаты испытаний in vivo, отмечено влияние присутствия стеклофазы в имплантатах на скорость регенерации кости и размеры имплантированных гранул биоматериала.